Politics and Theatre in Twentieth-Century Europe Imagination and Resistance - Morgan, Margot; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
This book explores the connection between politics and theatre by looking at the works and lives of Shaw, Brecht, Sartre, and Ionesco, providing a cultural history detailing the changing role of political theatre in twentieth-century Europe.
Keywords: Science; Science; Science, general